Depiction of Aging-Based Molecular Phenotypes With Diverse Clinical Prognosis and Immunological Features in Gastric Cancer - He, Fang; Ding, Huan; Zhou, Yang; Wang, Yuanzhen; Xie, Juan; Yang, Shaoqi; Zhu, Yongzhao (Frontiers in Medicine, 2022)
Objective: Aging acts as a dominating risk factor of human cancers. Herein, we systematically dissected the features of transcriptional aging-relevant genes in gastric cancer from multiple perspectives. Methods: Based on the transcriptome profiling of prognostic aging-relevant genes, gastric cancer patients in TCGA-STAD cohort were clustered with consensus clustering algorithm. Mutational landscape and chemotherapeutic responses were analyzed and immunological features (immunomodulators, immune checkpoint molecules, cancer immunity cycle and tumor-infiltrating immune cells) were systematically evaluated across gastric cancer. WGCNA was conducted for screening aging molecular phenotypes-relevant genes and key genes were identified with MCODE analyses. Expressions of key genes were examined in 20 paired tumors and controls with RT-qPCR and western blotting. Proliferation and apoptosis were investigated in two gastric cancer cells under MYL9 deficiency. Results: Three aging-based molecular phenotypes (namely C1, C2 and C3) were conducted in gastric cancer. Phenotype C1 presented the most prominent survival advantage and highest mutational frequencies. Phenotype C2 indicated low responses to sorafenib and gefitinib while C3 indicated low responses to vinorelbine and gemcitabine. Additionally, phenotype C2 was characterized by enhanced immune and stromal activation and an inflamed tumor microenvironment. Seven aging molecular phenotypes-relevant key genes (ACTA2, CALD1, LMOD1, MYH11, MYL9, MYLK and TAGLN) were identified, which were specifically up-regulated in tumors and in relation to dismal prognosis. Among them, MYL9 deficiency reduced proliferation and enhanced apoptosis in gastric cancer cells. Conclusion: Collectively, aging-based molecular subtypes may offer more individualized therapy recommendation and prognosis assessment for patients in distinct subtypes.